PENERAPAN MODEL PEMBELAJARAN POE (PREDICT- OBSERVE- EXPLAIN) UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA SEKOLAH DASAR - Irfan Ramadhani; Rusdial Marta; Mufarizuddin; Fadhilaturrahmi; Nurhaswinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the lack of mathematical reasoning ability in mathematics in grade IV of SDN 007 Bangkinang. One solution to overcome this problem is to apply the POE (Predict Observe-Explain) learning model. The purpose of this research is to improve reasoning ability in mathematics. This research method is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, and reflection. The research time was carried out in April-May 2024. The subjects of this research were 23 grade IV students. Data collection techniques were in the form of tests, observation and documentation. The results of the study showed that through the POE (Predict ObserveExplain) learning model, reasoning ability in mathematics was improved. This was shown before conducting the research, students' reasoning ability was 20%, then in cycle I meeting I increased to 55%, cycle I meeting II to 60%, then in cycle II meeting I to 77%, and cycle II meeting II increased to 84%. Thus, it can be concluded that using the POE (Predict Observe-Explain) learning model can improve the mathematical reasoning abilities of students in class IV of SDN 007 Bangkinang.